High-fidelity modeling of a vertical axis tidal turbine model under realistic flow conditions (Proceedings of the European Wave and Tidal Energy Conference, 2023)
In the context of the global energy crisis, developing renewable energies is of primal importance. Among the renewable resources available are tidal currents. Tidal currents can be exploited with tidal turbines. Different concepts of tidal turbine exist, we here investigate a vertical axis tidal turbine or VATT prototype made by HydroQuest and CMN. More precisely, we carry on numerical investigations on a Hydroquest/CMN tidal turbine model.Experimental studies are limited to turbine models and thus suffer from scale effects. In situ measurement are still expensive and difficult to acquire. Computational Fluid Dynamics (CFD) is an interesting alternative in order to go beyond what experiments can offer. One major drawback of CFD is that it requires validation of the models used. A validation of our CFD tool is included in this paper. Because the hydrodynamic of vertical axis tidal turbines is highly unsteady, Large Eddy Simulation (LES) are well adapted here.Blade-resolved Computational Fluid Dynamics (CFD) approaches are appropriate to study vertical axis tidal turbines, but their cost is still prohibitive for real size tidal turbine. Simplified approaches are preferred solutions. Literature showed that Actuator Line Model (ALM) LES is well suited to model vertical axis turbine.Most tidal sites are characterized with strong turbulence intensities. The presence of turbulence in most tidal sites has led companies and academics to study the effects of ambient turbulence over tidal turbines. It has been shown that turbulence can have a non-negligible influence on the turbine performances and wake. To account for the effects of turbulence, synthetic turbulence is introduced at the inlet of the simulation.The LBM is an unsteady weakly-compressible CFD approach. It solves the Boltzmann equation using an explicit time discretization and a uniform Cartesian grid called lattice. It has been proven to be an efficient approach for modeling tidal turbines using LES and ALM, Grondeau et al. (2019).In this paper, we study a tidal turbine model of the Hydroquest/CMN VATT using an ALM-LBM-LES approach. This model was tested at the Ifremer Boulogne-sur-Mer testing facilities. We first compare our results with the experimental ones in a scenario without turbulence and for flood and ebb tide configurations. A numerical investigation of the influence of upstream turbulence on the turbine performances and wake is then realized. Prospects of this study include among others the effects of turbines interactions and waves.